Gender Issues and Mathematical Performance at the Secondary Level: A Mauritian Experience. - Bessoondyal, Hemant; Malone, John (Key Centre for School Science and Mathematics, Curtin University of Technology, 2006)
Mathematics plays a fundamental role in the life of human beings. It promotes logical and rational thinking and enhances one's ability to analyze and to solve problems. Life without mathematics is almost an impossibility and it would be difficult "to live a normal life in very many parts of the world" without it (Cockcroft, 1982, p. 1). Its importance is also highlighted in the document entitled Principles and Standards for School Mathematics (National Council of Teachers of Mathematics, 2000, p. 5) where the following appears: "those who understand and can do mathematics will have significantly enhanced opportunities and options for shaping their future". Mathematics has been seen to act as a 'critical filter' in the social, economic and professional development of individuals. Mauritius relies, to a great extent, on its human resource power to meet the challenges of the technological developments a substantial core of mathematics is needed to prepare students for their involvements in these challenges. An analysis of the performance of boys and girls in mathematics in Mauritius proved to be important in view of equal participation of both sexes in the developments of the country and also achievement of gender equity.